Optimalisasi Keberlanjutan Water, Sanitation and Hygiene In School (WINs) dalam Meningkatkan Kesehatan dan Lingkungan Yang Bersih di Sekolah - Devi Angeliana Kusumaningtiar; Gisely Vionalita; Prita Dhyani Samilaksita; Namira Wadjir Sangadji; Taufik Rendi Anggara (I-Com: Indonesian Community Journal, 2024)
Sanitation problems that exist in developing countries are caused by several factors, namely the lack of attention given by the government to the sanitation sector, the lack of availability of clean water, the lack of clean behaviour, and inadequate sanitation in public places such as schools. This community service activity aims to improve water, sanitatin and hygiene in school (WinS) with the hope of improving the welfare and health of children in the school environment. This community service activity prioritises problems in WASH (water, sanitation and hygiene), namely low student knowledge about sanitation and hygiene, lack of hand washing soap and limited access to clean water. This community service method consists of several stages, namely the planning stage, preparation stage, implementation stage and evaluation stage. The results of this community service activity showed that there was an increase in the average knowledge of students about WASH by 0.26. Suggestions that can be given are to always give reminders to students about clean and healthy living behaviour, increase education through posters, leaflets and videos.